Creating Customer Loyalty Through Commitment to Quality of Service Model of Brady Cronin - Susriyanti, Susriyanti; Krisna, Nandan Lima; Lusiana, Lusiana; Nardo, Rio (ADPEBI Publisher, 2023)
Purpose –This study aims to see how the effect of the service quality of the Brady Cronin model (quality of interaction, quality of the physical environment, quality of results) on customer loyalty directly or indirectly through commitment. Methodology/approaches – This Study used Quantitatif method. The Quistioner were distributing to 200 customers of Bank Nagari in the city of Padang. Findings –It was found that the quality of the interaction and the quality of the physical environment in the service quality of the Brady Cronin model directly affected customer loyalty. Meanwhile, the quality of the results in the service quality of the Brady Cronin model does not directly affect customer loyalty. Indirectly, the three services of the Brady Cronin model of service quality affect customer loyalty through commitment. Novelty/values ​​–The quality of results that do not have a direct effect on loyalty indicates that customers have not got what they want. So it is important for Bank Nagari to improve the quality of results to increase customer loyalty in the future.